PERBEDAAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA YANG MENDAPATKAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY DENGAN YANG MENDAPATKAN MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER (Mosharafa: Jurnal Pendidikan Matematika, 2013)
Abstract:Quasi experiment studies with experimental design ( the statistic group posttes design) aimed to determine differences in mathematical problem solving ability of students get the learning model two stay two stray with again learning model Numbered Head Together, as well as the attitude of students towards learning mathematics for teaching model Two stay Two stray with learning model Numbered Head Together. Data analysis can be carried out with test data normality. Mann whitney. The results of this study indicate : (1) there is a difference mathematical problem solving ability of students get the learning model Two stay two stray with a gain learning model Numbered Head Together; (2) student’s attitudes toward learning model Two stay Two stray and learning model Numbered Head Together in general the students to be kind to both the learning model.Abstak: Penelitian kuasi eksperimen dengan desain eksperimen (the statistic group posttes design) bertujuan untuk mengetahui perbedaan kemampuan pemecahan masalah matematis siswa yang mendapatkan model pembelajaran Two stay Two Stray dengan yang mendapatkan model pembelajaran Numbered Head Together, serta mengetahui sikap siswa terhadap pembelajaran matematika terhadap model pembelajaran Two stay Two Stray dengan model pembelajaran Numbered Head Together. Analisis data dilakukan dengan uji normalitas data, Mann Whitney. Hasil penelitian ini menunjukan bahwa: (1) terdapat perbedaan kemampuan pemecahan masalah matematis siswa yang mendapatkan model pembelajaran Two stay Two Stray dengan yang mendapatkan model pembelajaran Numbered Head Together; (2) sikap siswa terhadap model pembelajaran Two stay Two Stray dan model pembelajaran Numbered Head Together secara umum siswa bersikap baik terhadap kedua model pembelajaran tersebut.